PENGARUH KUALITAS PELAYANAN WEBSITE DJP TERHADAP KEPUASAN PENGGUNA DENGAN MODIFIKASI E GOVQUAL - Ari, Dessanti Putri Sekti; Hanum, Latifah (FIA UB, 2021)
One of the DGT e-government is the DGT website.. The DGT website contains the latest information on taxes , announcements, tax applications,Â the latest laws and regulations, press releases, DGT activities, customer service, and information about the DGT organizational structure. The existence of the website is expected to facilitate communication between taxpayers and the tax authorities as well as a means of facilitating the public to get the latest information related to taxation in Indonesia. However, some people still complain about this website service, one of which is that the website is still difficult to access. This complaint can potentially reduce user satisfaction. Therefore, this study aims to determine the effect of service quality on user satisfaction of the DGT website with e govqual modification. The dimensions used to measure this service's quality are efficiency, trust, reliability, citizen support, and system quality.Â Students are one of the DGT website users. Therefore, the population in this study were active undergraduate taxation students. The sampling method used was a random sampling system. This study uses an online survey to obtain data. The statistical tool used in this research is the SmartPLS program. This study's results indicate that each of the e govqual dimensions and its significant modification forms the system quality variable. And system quality variables affect user satisfaction.